Lobectomy sufficiency for 1–4 cm differential thyroid cancer: a large retrospective study in China - Jun Xu; Qixian Yao; Zhongliang Wu; Wenhuan Dou; Yujing Liu (Scientific Reports)
Abstract This study aimed to determine whether lobectomy is appropriate for the long-term prognosis of 1–4-cm-sized differential thyroid cancer (DTC). This retrospective study included 2,178 patients with 1–4-cm DTC treated via thyroid lobectomy (LT) or total or near-total thyroidectomy (TT) and who were followed up for at least 3 years. The primary endpoint was a structural incomplete response, which was confirmed via imaging with or without a positive histological or cytological examination. Subgroup analysis was performed according to tumor size. LT was performed in 1,535 patients (70.48%), and TT was conducted in the remaining 643 (29.55%) patients. During an average follow-up period of 48.08 months, the recurrence rate was 7.2% in the LT group and 5.3% in the TT group, which was not significantly different (p = 0.108). There were no significant differences in disease-free survival between both groups (hazard ratio, 1.394; 95% confidence interval, 0.9761–1.990; p = 0.089). In the subgroup analysis, the recurrence rates in the LT group were higher than those in the TT group for both the 2–3-cm (13.6% vs. 2.6%, p < 0.01) and 3–4-cm categories (20.6% vs. 4.8%, p < 0.01). For 1–2-cm DTC, surgeons can choose LT or TT owing to their similar recurrence rate, whereas for 2–4-cm DTC, TT is preferred.